2017
DOI: 10.1186/s12879-017-2200-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the Xpert MTB/RIF test on the time to MDR-TB treatment initiation in a rural setting: a cohort study in South Africa’s Eastern Cape Province

Abstract: BackgroundThere are significant delays in initiation of multidrug-resistant tuberculosis (MDR –TB) treatment. The Xpert MTB/RIF test has been shown to reduce the time to diagnosis and treatment of MDR-TB predominantly in urban centres. This study describes the time to treatment of MDR-TB and the effect of Xpert MTB/RIF on time to treatment in a deprived rural area in South Africa.MethodsThis was a retrospective cohort study analysing the medical records of patients diagnosed with MDR-TB in King Sabata Dalindye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 28 publications
(59 reference statements)
0
29
2
Order By: Relevance
“…This compares well with the median delay-time of 13 days (IQR 7-28) and 15 days (IQR 8-23) reported in Johannesburg and in the Eastern Cape in South Africa, respectively. In a Cape Town study, Cox et al found a relatively shorter median time to treatment initiation of eight days [9][10][11][12] . In these studies, time to treatment initiation was measured from sputum submission at the laboratory while we measured it from the availability of a positive Xpert MTB/RIF assay result with rifampicin resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This compares well with the median delay-time of 13 days (IQR 7-28) and 15 days (IQR 8-23) reported in Johannesburg and in the Eastern Cape in South Africa, respectively. In a Cape Town study, Cox et al found a relatively shorter median time to treatment initiation of eight days [9][10][11][12] . In these studies, time to treatment initiation was measured from sputum submission at the laboratory while we measured it from the availability of a positive Xpert MTB/RIF assay result with rifampicin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the impact of the Xpert MTB/RIF assay on initiation of drug resistant TB treatment remains unknown. Studies from South Africa reported substantial delays for treatment initiation and high rates of suboptimal treatment for patients diagnosed with RR-TB when initiating treatment based solely on the Xpert MTB/ RIF result [8][9][10] .…”
mentioning
confidence: 99%
“…Our study findings were similar to previous studies showing that Xpert assay reduced time to MDR-TB treatment initiation. [16][17][18][19] However, early treatment initiation was not associated with treatment success, which may explain the lack of improvement in clinical outcomes. Our study agrees with recent studies demonstrating that use of Xpert has not reduced early mortality in rifampicin-resistant patients.…”
Section: Researchmentioning
confidence: 99%
“… 27 Recently, Iruedo et al found that diagnostic modality (GeneXpert, Line Probe Assay, culture) reduced the time for diagnosis of individuals treated in a rural South African setting; however, modality did not affect time from diagnosis to treatment initiation, which was a median of 14 days, similar to results in other studies. 28 , 29 Although age was assessed as a factor in these studies, neither compared youth with adults.…”
Section: Discussionmentioning
confidence: 99%